GEODIVERSITY GUNUNG API JABOI KOTA SABANG - Br Sembiring, Tesalonika; Ramadanika, Ramadanika; Imam, Muhammad; Silalahi, Enjelina Tiurma Br; Nanda, Nur Rahma; Syafira, Amelia (Program Studi Pendidikan Geografi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Samudra, 2024)
Reviewing geological diversity (geodiversity) in an area is important to review as a candidate for a geopark area. Jaboi volcano on Sabang Island is a type C volcano which shows volcanic activity in the form of mud and sulfur craters in it, on Sabang Island which Formed as a result of volcanic activity, Mount Seulawah is related to the existence of the Jaboi Type C volcano which is on a coastal island.